Hubungan Antara Tingkat Kecemasan dan Compulsive Buying Disorder pada Mahasiswa Preklinik Fakultas Kedokteran - Silviany, Clarisa; Agus, Dharmady; Mahaputra, Mahaputra (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: At a certain level, excessive anxiety could lead to anxiety disorders and adversely affect daily life. Medical students had a higher prevalence of anxiety disorders than the general population. This anxiety might lead to negative behavioral tendencies and certain mental disorders, such as Compulsive Buying Disorder (CBD). This study aimed to determine whether there was an association between anxiety level and CBD among preclinical students of the Faculty of Medicine.Method: This research was an analytic observational study which was conducted using a cross-sectional study method on 107 preclinical students of Faculty of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia as respondents by filling out the Depression Anxiety Stress Scale (DASS-42) and Revised Edwards Compulsive Buying Scale (ECBS-R) questionnaire. The data was analyzed using the Chi-square test.Results: The results of statistical tests showed that there was a significant relationship between anxiety levels and CBD with p less than 0.001. The results showed that the prevalence of anxiety disorders in preclinical students was 33.6%, with the highest prevalence being at moderate anxiety levels (16.8%), and the prevalence of CBD was 25.2%.Conclusion : In conclusion, there was an association between the level of anxiety and CBD among preclinical students of the faculty of medicine.